Gambaran Achievement Motivation Pada Mahasiswa Keperawatan Universitas Padjadjaran - Yosep, Iyus; Shaumy, Bella Nadya; Harun, Hasniatisari; Mardhiyah, Ai (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Nursing students are faced with achievement motivation challenges that can affect their academic and professional development. Contributing factors are high academic pressure, lack of social support, and low perception of the relevance of academic tasks in the nursing context. To describe achievement motivation in nursing students.  This study used a descriptive approach with data collection through the distribution of achievement motivation scale questionnaires that have been adapted for the nursing context. The research sample involved 270 active semester nursing students, and data analysis was carried out using descriptive statistics, specifically univariate analysis. The authors found that there were 184 students with a moderate level of achievement motivation (68.15%), 41 students had high achievement motivation (15.19%), and 45 students with low achievement motivation (16.67%). This shows that nursing students need to increase achievement motivation to adapt to the learning process. This study is expected to provide practical guidance for educational institutions and nursing practitioners in improving achievement motivation and well-being of nursing students. Keywords: Achievement Motivation, Nursing, Students  ABSTRAK Mahasiswa keperawatan dihadapkan pada tantangan achievement motivation yang dapat memengaruhi perkembangan akademis dan profesional mereka. Faktor-faktor penyebabnya adalah tekanan akademis yang tinggi, kurangnya dukungan sosial, dan persepsi yang rendah terhadap relevansi tugas-tugas akademis dalam konteks keperawatan. Untuk menggambarkan achievement motivation pada mahasiswa keperawatan. Penelitian ini menggunakan pendekatan deskriptif dengan pengumpulan data melalui distribusi kuesioner achievement motivation scale yang telah diadaptasi untuk konteks keperawatan. Sampel penelitian melibatkan 270 mahasiswa keperawatan semester aktif, dan analisis data dilakukan dengan menggunakan statistik deskriptif, khususnya analisis univariat. Penulis menemukan bahwa terdapat 184 mahasiswa dengan tingkat achievement motivation sedang (68.15%), 41 mahasiswa memiliki achievement motivation tinggi (15.19%), dan 45 mahasiswa dengan achievement motivation rendah (16.67%). Hal ini menunjukkan bahwa mahasiswa keperawatan perlu meningkatkan achievement motivation untuk beradaptasi dalam proses pembelajaran. Penelitian ini diharapkan dapat memberikan panduan praktis bagi institusi pendidikan dan para praktisi keperawatan dalam meningkatkan motivasi berprestasi dan kesejahteraan mahasiswa keperawatan. Kata Kunci: Achievement Motivation, Keperawatan, Mahasiswa